Can Simulator Sickness Be Avoided? A Review on Temporal Aspects of Simulator Sickness - Dużmańska, Natalia; Strojny, Paweł; Strojny, Agnieszka (Frontiers in Psychology, 2018)
Simulator sickness is a syndrome similar to motion sickness, often experienced during simulator or another virtual reality (VR) exposure. Many theories have been developed or adapted from the motion sickness studies, in order to explain the existence of the syndrome. The simulator sickness can be measured using both subjective and objective methods. The most popular self-report method is the Simulator Sickness Questionnaire. Attempts have also been made to discover a physiological indicator of the described syndrome, but no definite conclusion has been reached on this issue. In the present paper, three temporal aspects of the simulator sickness are discussed: the time range of simulator sickness tolerance, possibility of adapting VR users in advance and persistence of the symptoms after VR exposure. Evidence found in 39 articles is widely described. As for the first aspect, it is clear that in most cases severity of the simulator sickness symptoms increases with time of exposure, although it is impossible to develop a single, universal pattern for this effect. It has also been proved, that in some cases a threshold level or time point exists, after which the symptoms stop increasing or begin to decrease. The adaptation effect was proved in most of the reviewed studies and observed in different study designs – e.g. with a couple of VR exposures on separate days or on one day and with a single, prolonged VR exposure. As for the persistence of the simulator sickness symptoms after leaving the VR, on the whole the study results suggest that such an effect exists, but it varies strongly between individual studies – the symptoms may persist for a short period of time (10 minutes) or a relatively long one (even 4 hours). Considering the conclusions reached in the paper, it is important to bear in mind that the virtual reality technology still evokes unpleasant sensations in its users and that these sensations should be cautiously controlled while developing new VR tools. Certainly, more research on this topic is necessary.